Phenothiazine-based CaaX competitive inhibitors of human farnesyltransferase bearing a cysteine, methionine, serine or valine moiety as a new family of antitumoral compounds. Issue 20 (15th October 2015) - Dumitriu, Gina-Mirabela; Bîcu, Elena; Belei, Dalila; Rigo, Benoît; Dubois, Joëlle; Farce, Amaury; Ghinet, Alina
Graphical abstract: Abstract: A new family of CaaX competitive inhibitors of human farnesyltransferase based on phenothiazine and carbazole skeleton bearing al -cysteine, l -methionine, l -serine orl -valine moiety was designed, synthesized and biologically evaluated. Phenothiazine derivatives proved to be more active than carbazole-based compounds. Phenothiazine1b with cysteine residue was the most promising inhibitor of human farnesyltransferase in the current study.